Fluid flow and fault-related subsurface fractures in slate and metasandstone formations: A case study of the Jentse Geothermal Area, Taiwan. (January 2021) - Chen, Bing-Cheng; Perdana, Tito; Kuo, Li-Wei
Highlights: This study used open-hole and image logs in the slate belt of Taiwan to identify conductive fractures in tight rocks. One major fault system with three conductive fault zones was identified in this study. The borehole images show the conductive fault zones mainly consist of permeable fault cores and fractured damage zones. The most conductive fluid conduits would be the faults penetrating metasandstone with small displacements. Abstract: Permeable structures associated with faults are commonly treated as geothermal fluid conduits in most tight geothermal reservoirs. However, the properties of permeable structures within fault zones remain unclear due to the lack of subsurface geological data, e.g., the geothermal systems in the tight slate and metasandstone formations in Northeastern Taiwan. This study presented standard open-hole and Fullbore Formation MicroImager (FMI) logs acquired in the 8.5-inch-diameter section of the JT-3 well (800–1475 m measured depth) in the Jentse geothermal area, Taiwan, to identify the subsurface fracture structures and the possible pathway of fluid flow. Using open-hole log data, we generate a lithology interpretation for the borehole and model the associated effective porosity. Based on the FMI images, four types of natural open fractures, two types of natural sealed fractures, and drilling-induced tensile fractures were identified. Integration of the lithological model, the effective porosity, and the types of fractures reveals one major permeable fault system comprising three permeable fault zones. The fault system is composed of both permeable fault cores marked by porous fault breccia and damage zones characterized by a large number of open-fracture planes. The static borehole temperature log also shows deflections in these interpreted permeable fractures zone. Deflections in these fracture zones that, based on petrophysical and borehole image logs, are interpreted as permeable. According to the orientations of the bed boundaries and fault planes obtained from FMI images, the fault system may have an orientation of N50–70 °E and dips 70–90˚ to the NW with a width of around 116 m. This study illustrates how subsurface structures control geothermal conduits. The concept and workflow of this study may be useful for other fault-controlled geothermal areas in Taiwan.